2018–2019 Florida Citrus Production Guide: Soft-Bodied Insects Attacking Foliage and Fruit - Philip A. Stansly; Jawwad A. Qureshi; Lukasz L. Stelinski; Lauren M. Diepenbrock; Michael E. Rogers (EDIS)
This 5-page fact sheet is part of the 2018–2019 Florida Citrus Production Guide. This section is focused on sucking insects which affect foliage, twigs, and fruit of citrus in Florida. Insects covered here include scales, mealybugs, whiteflies, and aphids that can impact the health of young and mature trees and fruit quality. They differ from each other in their biology, generation times, and injury to plant, but approaches to monitoring and management are similar. Individual discussions of some groups are provided, and the tables of management options are organized by active ingredient, with the target pests from this chapter in bold text. Written by P. A. Stansly, J. A. Qureshi, L. L. Stelinski, L. M. Diepenbrock, and M. E. Rogers, and published by the Department of Entomology and Nematology, May 2018.